Consumer Migration From Physical Formats to Digital Music in Indonesia - Ronaldy Bintang Nugraha (Borong Newinera Publisher, 2023)
Changes in technology and consumer preferences have shifted the way people listen to and access music. This phenomenon has had a major impact on record labels, artists, and the way music is distributed. The purpose of this study is to understand and analyze the process of consumer migration from physical format to digital music in Indonesia. This research method is qualitative research. The data collection technique in this research is a literature study. The data that has been collected is then analyzed using data reduction techniques, data presentation and conclusion drawing. The results showed that music formats began with vinyl records, cassettes, compact disks (CDs), MP3s, and digital music. Consumer migration from physical formats to digital music in Indonesia is an unavoidable trend. This trend is caused by several factors, including ease and convenience, price, and a wider collection.